How authentic is language included in English and German language textbooks for primary education in Poland? A case study - Budzyńska, Paula (Glottodidactica, 2018)
This study aims at investigating the authenticity of vocabulary and grammar structures included in two selected English language textbooks (hereafter ELTs) and two German language textbooks (hereafter GLTs) for the first stage of education in Poland. In order to achieve the assumed objective, the author examined literary materials, that is, songs, rhymes, or short stories, included in selected ELTs and GLTs in accordance with the principles of the corpus stylistics method developed, for example, by Semino & Short (2004), Mahlberg (2014), or McIntyre (2015). With the support of BYU-BNC and DWDS corpora, the performed analysis indicated, for instance, that in the case of both types of textbooks studied, the number of authentic words that children are to learn seems to be rather insufficient. The outcomes of the study enable suggesting certain modifications targeted at the increase of the authenticity of language that the analysed textbooks include.